Finite-time stabilisation of some power transmission systems. (February 2019) - Ayari, Mohamed; Belhaouane, Mohamed Moez; Jammazi, Chaker; Braiek, Naceur Benhadj; Guillaud, Xavier
This paper presents the finite time stabilisation strategy of two problems: the first one is the control of the high voltage direct current based on voltage source converter, while the second is the control of the multi-terminal direct current transmission systems. Subject to finite-time control design strategy, a linear and nonlinear dynamic model are derived based on the state-space description. Furthermore, continuous or discontinuous finite-time feedbacks are proposed to ensure the tracking of the output variables and to enhance the stability of the studied high voltage direct current system. In addition, the proposed control strategy is extended for the multi-terminal direct current system. A comparative study between various approaches (Proportional-Integral control, continuous or discontinuous stabilising finite-time controllers and control by backstepping) is presented and shows that the finite-time continuous feedback gives an excellent transient response.